Peculiarities of the cytological picture in the periodontitis tissues in patients with generalized periodontitis and bronchial asthma on the background of glucocorticosteroid therapy. - Babenko, V. M. (Морфологія / Morphologia / Morfologìâ, 2011)
The study is devoted to the issues of peculiarities of cytological parameters in periodontitis tissues in patients with generalized periodontitis and bronchial asthma on the background of glucocorticosteroid therapy. Comparative analysis of clinical course, cytological and cytometric parameters proved the efficiency of using miramistin ultrasonophoresis and miramistin application. Correlative analysis of 126 patients was carried out. It has been found out that bronchial asthma and glucocorticosteroid therapy negatively influence the course of generalized periodontitis decreasing the manifestation of the inflammatory reaction and causing more significant cytological changes in periodontitis tissue epithelium, such as dystrophy, necrosis and necrobiosis. We were the first to carry out the comparative analysis of efficiency of using miramistin in preventive treatment of patients with generalized periodontitis and bronchial asthma on the background of glucocorticosteroid therapy. We have arrived to the conclusion that miramistin ultrasonophoresis takes a shorter time to act and produces a more prolonged effect than miramistin application. This effect is confirmed by normalization of cytological parameters of periodontitis tissues.